Attenuation of pain and inflammation induced in mice treated orally with crude extract of Aloysia polystachya (Griseb.) Moldenke (Verbenaceae) - Mariela Ortiz, Isabelle Wilson, Yenny Montalbetti, Olga Heinichen, Wilfrido Arrúa, Nelson Alvarenga, Derlis A. Ibarrola, María del Carmen Hellión-Ibarrola (Journal of Applied Pharmaceutical Science, 2022)
The objective of this work was to determine the analgesic and anti-inflammatory activity of Aloysia polystachya (Griseb.) Moldenke (Verbenaceae) in experimental models of acute pain and inflammation in mice. Methods of pain induced by caudal pressure (Randall-Selitto), chemical stimulation (acetic acid or the writhing test), and thermal stimulation (hot plate) were used to study analgesic effects. Additionally, edema of the paw induced by injection of 1% carrageenan was used to evaluate the anti-edema activity of A. polystachya. Oral doses of 100 and 200 mg/kg of crude extract of A. polystachya (CEAp) significantly reduced the sensibility to painful stimuli induced by the application of pressure in the tail comparable with an analgesic effect (p < 0.05) in a non-dose dependent manner. Additionally, the number of abdominal contortions was significantly reduced in comparison with the control group and with similar strength to the group treated with Indomethacin 10.0 mg/kg. Similarly, in the model of pain induced by thermal stimulation, it was observed that the groups treated with CEAp presented statistically significant analgesic activity in comparison with the control group and with a similar intensity to the group treated with morphine 6.0 mg/kg. Finally, a statistically significant reduction of edema induced by 1% carrageenan was observed with oral administration of 100 mg/kg of CEAp in comparison to the positive control of edema in a manner similar to the group treated with Indomethacin 10 mg/kg. Based on these results, it was concluded that the CEAp possesses the capacity to increase pain threshold in three pre-clinical models of pain induced (mechanical pressure, chemically and thermally) in mice, compatible with an analgesic effect. Also, CEAp demonstrated antiedematous capacity in carrageenan-induced paw edema in mice, concordant with anti-inflammatory effect using the plethysmography method. These pharmacological effects are potentially due to the presence of verbascoside in CEAp. Additionally, these experimental results are correlated with the popular use of CEAp and present a variety of opportunities for pharmaceutical research such as the development of innovative phytopharmaceuticals.
Keywords: Aloysia polystachya, analgesia, Randall-Selitto, abdominal contortions, hot plate, plethysmometer